2017
DOI: 10.2147/copd.s130353
|View full text |Cite
|
Sign up to set email alerts
|

Patient-perceived treatment burden of chronic obstructive pulmonary disease

Abstract: BackgroundWhile chronic morbidity and mortality from COPD is well documented, little is known about the treatment burden faced by patients with COPD.Subjects and methodsPatients with severe airflow obstruction (forced expiratory volume in 1 second [FEV1] <50% predicted) representing different age-groups, sex, and number of comorbidities participated in a semistructured interview. Interviews were conducted until thematic saturation was reached. Interviews were recorded, transcribed, and analyzed thematically us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…Many patients who do not adhere to prescribed treatments, however, say that they know that they should do differently but that they lack the information and support to do so 7. Patients will also reject medical advice if the perceived benefit is considered insufficient in relation to the required investment of time, energy, and cost 8. These assessments about return on investment may be done consciously or intuitively, particularly when patients are overburdened by their treatment workload.…”
Section: Consequences Of Overburdenmentioning
confidence: 99%
“…Many patients who do not adhere to prescribed treatments, however, say that they know that they should do differently but that they lack the information and support to do so 7. Patients will also reject medical advice if the perceived benefit is considered insufficient in relation to the required investment of time, energy, and cost 8. These assessments about return on investment may be done consciously or intuitively, particularly when patients are overburdened by their treatment workload.…”
Section: Consequences Of Overburdenmentioning
confidence: 99%
“…But a randomized controlled trial demonstrated that most patients with COPD (ie, all except a subset of the highest risk patients) derive no benefit from the oxygen-not in terms of survival, hospital admissions, or quality of life. 2 At the same time, oxygen significantly increases the risk of burns for patients; 3 it is costly to the patient; 4 and it is a burden that the patient literally has to carry that impairs their ability to socialize. 4 Other well-publicized examples of low-value care include hormone replacement therapy to prevent cardiovascular events among perimenopausal women; 5 antibiotics to treat viral upper-respiratory infections; and diagnostic imaging for simple lower-back pain.…”
Section: Equity Underuse and Overusementioning
confidence: 99%
“…2 At the same time, oxygen significantly increases the risk of burns for patients; 3 it is costly to the patient; 4 and it is a burden that the patient literally has to carry that impairs their ability to socialize. 4 Other well-publicized examples of low-value care include hormone replacement therapy to prevent cardiovascular events among perimenopausal women; 5 antibiotics to treat viral upper-respiratory infections; and diagnostic imaging for simple lower-back pain. 6 In each of these examples, research evidence demonstrates that care provides no benefits or potential ben-efits are outweighed by known harms.…”
Section: Equity Underuse and Overusementioning
confidence: 99%
“…As indicated by the results of the present study, there was a significant association 007). It was observed that right lower abdominal pain was the most frequent presentation among the patients with different marital status, followed by epigastric pain Table (13).…”
Section: Resultsmentioning
confidence: 99%